Pokerfaced : Flemish and Dutch Baroque Faceds Unveiled - Van der Stighelen, Katlijne; Magnus, Hannelore; Watteuw, Bert (Turnhout : Brepols, 2010)
Section I: Emotion and Expression; Section II: Stage and Performance; Section III: Kinship and Recognition; Section IV: Intimacy and Remembrance
Engelse titel, Engelse, Duitse en Nederlandse teksten
boek